Ekranisasi Novel Ke dalam Film Matt And Mou Karya Wulanfadi: Sebuah Kajian Sastra Bandingan - Citraria Citraria; I Made Suyasa; Linda Ayu Darmurtika; Roby Mandalika Waluyan (Universitas Muhammadiyah Mataram, 2023)
This study aimed to: (1) describe the form of novel ecranization of Matt and Mou into the Matt and Mou movie in terms of plot, setting, and characterizations; and (2) describe the similarities and differences between the novel and film of Matt and Mou in terms of plot, background, and characterization. The literature study method was used to collect data, and the documentary method was then descriptively analyzed The study showed three types of ecranization in novels and movies: reduction, addition, and varying changes. The reduction emphasizes characterization elements, the adition emphasizes plot elements, and the various changes emphasize background elements. When the novel is filmed some of the characterizations are disappeared. The director also made additional plots in the movie, and it is different from the plot in the novel. The various changes in the movie are three settings. In addition to the form of ecranization, similarities and differences also appear in novels and movies. There are 22 characters in the novel on the contrary, there are only eight characters in the movie. Overall the characterizations in the movie are almost the same as the charactenzations in the novel except for one additional character that is not in the novel. The plot used in the novel is a mixed plot, while in the movie, it uses a forward plot. and some of the settings in the novel are also used in the movie.